Factors Of The Formation Of New Autonomous Regions And Its Impact On State Finances - Arief Maulana (Jurnal Ekonomi Pembangunan, 2019)
The purpose of this study is to analyze the driving factors of the formation of new autonomous regions in Indonesia during the reformation era and its impact on state finance. This study is a policy study by collecting data and then analyzing it into a conclusion and recommendation. This type of study is a literature study with the method used is descriptive qualitative method. The results of the study show that since the reform era, the formation of a new autonomous region has been very massive. If calculated on average from 1999 to 2014, each year the new regions increase by 13 regions per year. The formation of the new autonomous regions requires considerable preparation and costs, starting from the initial formation to the implementation. In addition, in general the new autonomous regions show higher fiscal dependencies than the old regions. Thus, it can be stated that the establishment of the new autonomous regions has caused pressure on the state finances due to the large amount of funds that must be transferred to new regions.